Uniform Cooling of a Flat Surface by an Optimized Array of Turbulent Impinging Air Jets. Issue 20 (14th December 2019) - Sedighi, Erfan; Mazloom, Ali; Hakkaki-Fard, Ali
Abstract: The aim of this study is to investigate the uniform cooling of a hot isothermal heated target surface, using four turbulent impinging air jets. Eight parameters including the width of jets, the space between the inner jets, the space between inner and outer jets, the distance of jets from the plate, the impingement angle of jets, and the overall volumetric flow rate of the cooling air per unit depth of the nozzle are considered as design variables. The normalized standard deviation of the local Nusselt number from the desired Nusselt number is considered as the objective function. An optimization algorithm based on pattern search method is utilized to obtain the optimum array of the jets. Two different scenarios of the problem are considered, one with fixed normal impingement angles and the other with the optimized angles. Results show an almost uniform distribution of the local Nusselt number. Increasing the amount of desired Nusselt number for the case with fixed impinging angles results in a higher Reynolds number, a wider opening for outer jets and a reduction in jet to jet and jet to surface distances. However, changes in design parameters for the case with optimum impinging angles are erratic.